SEROPREVALENCE OF INFECTIOUS BURSAL DISEASE VIRUS IN PRIVATE POULTRY BREEDINGS OF UKRAINE FROM 2014 TO 2016 - А. С. Пастиря; І. О. Собко; Є. О. Шайхет; В. П. Поліщук (Mìkrobìologìâ ì Bìotehnologìâ. Мікробіологія і біотехнологія, 2017)
Aim. Implementation of serological monitoring of infectious bursal disease virus in poultry households to study the relevance of this pathogen in Ukraine. Methods. Presence of IBDV antibodies was analyzed in 83 farms of 20 regions of Ukraine. Overall 20,126 serum samples from selected chicken (Gallus domesticus) which ages ranged from 1 to 506 days were analyzed. For the IBDV antibodies detection there were used the indirect ELISA method, which was carried out using commercial test kits IDEXX IBD (USA). The optical absorbance value was determined by wavelength of 650 nm. Antibody titers were calculated using software xCheck (USA). Titer values above 396 were considered as positive. Results. IBDV antibodies were found in the serum of chickens from all the analyzed farms and regions of Ukraine. Antibodies were detected in 19.236 samples of blood serum. The value of antibody titers in positive samples varied from 415 to 15576. Mean titers were 5952. The percentage of positive samples in different areas was very high and ranged from 82.5% in the Kherson region to 100% in the Chernihiv, Poltava and other regions. IBDV antibodies were detected in all age groups of birds. The maximum level of maternal antibodies were observed at 1–4 days after birth. Conclusions. We have shown the significant spread of IBDV in Ukraine. These data suggest the need to strengthen of biosecurity and management in order to prevent the spread of the virus in the farms.